PixelLab Media to Improve Spatial Thinking Skills of Class XI Students at MAN 3 Parigi - Uswatun Hasanah; Haslita Rahmawati Hasan; Suwarni Suwarni; Risma Fadhila Arsy (FKIP - Universitas Riau, 2026)
Spatial thinking is an important competency in Geography learning because students need to understand location, distribution, patterns, and spatial relationships. However, students at MAN 3 Parigi still experienced difficulties in understanding spatial concepts, partly because learning was dominated by conventional methods and limited digital media. This study aimed to analyze the effect of PixelLab media on the spatial thinking skills of Class XI students in learning the distribution of disasters in Indonesia. A quantitative quasi-experimental method with a Nonequivalent Control Group Design was employed. The participants were 51 students, consisting of 26 students in the experimental class and 25 students in the control class. Data were collected using a spatial thinking skills test administered as a pretest and posttest to both groups. The same instrument was used before and after the treatment to measure changes in students' spatial thinking skills.The experimental class achieved a higher posttest mean than the control class, and the difference was statistically significant. The findings indicate that PixelLab-supported learning can help students visualize, classify, compare, and communicate geographic information. Therefore, PixelLab can be used as an alternative digital learning medium to support the development of spatial thinking skills in Geography learning.